Expression of basic fibroblast growth factor in synovial tissues from patients with rheumatoid arthritis: detection by immunohistological staining and in situ hybridisation. Issue 1 (January 1994) - Nakashima, M; Eguchi, K; Aoyagi, T; Yamashita, I; Ida, H; Sakai, M; Shimada, H; Kawabe, Y; Nagataki, S; Koji, T
Abstract : OBJECTIVE–The distribution and production of basic fibroblast growth factor (bFGF) was examined on the synovium from patients with rheumatoid arthritis (RA) and osteoarthritis (OA). METHODS–The localisation of bFGF was determined by an immunohistochemical staining procedure using anti-bFGF monoclonal antibody. The expression of bFGF mRNA was detected by nonradioactive in situ hybridisation using bFGF antisense oligo DNA. RESULTS–The bFGF was found in the synovial lining cell, sublining stromal fibroblast-like cells, and vascular endothelial cells from patients with RA and OA. Little or no bFGF was found in non-inflamed synovium. Immunostaining of bFGF in the synovial cells was more extensive and intense in synovium of patients with RA than that of patients with OA. The nuclei of the synovial lining cell layer were also immunostained. These nuclear staining were more intense in the lining cell layer from RA patients with moderate or severe proliferation of synovial cells than in RA patients with mild proliferation. The bFGF mRNA was also detected in the synovial lining cell layer of the inflamed synovium. CONCLUSION–The synovial lining cells produced bFGF. The proliferation of synovial cells in the inflamed joints may be the results of stimulation by the bFGF in autocrine manner.